2015
DOI: 10.1371/journal.pone.0124828
|View full text |Cite
|
Sign up to set email alerts
|

ESAT-6 Targeting to DEC205+ Antigen Presenting Cells Induces Specific-T Cell Responses against ESAT-6 and Reduces Pulmonary Infection with Virulent Mycobacterium tuberculosis

Abstract: Airways infection with Mycobacterium tuberculosis (Mtb) is contained mostly by T cell responses, however, Mtb has developed evasion mechanisms which affect antigen presenting cell (APC) maturation/recruitment delaying the onset of Ag-specific T cell responses. Hypothetically, bypassing the natural infection routes by delivering antigens directly to APCs may overcome the pathogen’s naturally evolved evasion mechanisms, thus facilitating the induction of protective immune responses. We generated a murine monoclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…We found that the ASB nontreated preparation but not the ASB‐treated one was able to induce higher level of IFN‐γ secretion. Interestingly, we noted that studies reporting the induction of IFN‐γ secretion by ESAT‐6 either used the form bound to CFP‐10, purified from Mtb cell culture supernatant , or ESAT‐6‐derived small peptides . Other groups using recombinant forms of ESAT‐6, without adding a washing step with ASB to their purification protocols, also found that such a form did induce the secretion of IFN‐γ by TB patientT cells .…”
Section: Discussionmentioning
confidence: 99%
“…We found that the ASB nontreated preparation but not the ASB‐treated one was able to induce higher level of IFN‐γ secretion. Interestingly, we noted that studies reporting the induction of IFN‐γ secretion by ESAT‐6 either used the form bound to CFP‐10, purified from Mtb cell culture supernatant , or ESAT‐6‐derived small peptides . Other groups using recombinant forms of ESAT‐6, without adding a washing step with ASB to their purification protocols, also found that such a form did induce the secretion of IFN‐γ by TB patientT cells .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have attempted to improve DC function at the time of vaccination by targeting the CD40 activation pathway49, DC receptor Dec-205 (refs 50, 51), or by utilizing cell-derived vaccines, such as Mtb antigen-primed DCs3132. Improving DC function by targeting the CD40 pathway during vaccination had no effect49, while activating Dec-205 at the time of vaccination had a small effect (∼0.5 log reduction) on vaccine-induced protection on Mtb challenge5051.…”
Section: Discussionmentioning
confidence: 99%
“…Improving DC function by targeting the CD40 pathway during vaccination had no effect49, while activating Dec-205 at the time of vaccination had a small effect (∼0.5 log reduction) on vaccine-induced protection on Mtb challenge5051. Vaccination with antigen-primed DCs has generated mixed results in Mtb -infected mice, with a study demonstrating a negative impact of DC vaccination due to exuberant inflammation31, or induction of vaccine-induced protection similar to levels seen in BCG-vaccinated hosts32.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, determining which human APC subset in different tissues is the most efficient one for sensing ESAT-6 might enable the development of improved strategies aimed at the targeted delivery of TB vaccines to a particular APC subset (73,74) and lead to optimal and localized IL-18-mediated IFN-γ secretion. Another critical question arises from our study: how does ESAT-6 activate NLRP3 in vivo?…”
Section: 1mentioning
confidence: 99%